Dispersion Composition and Dispersant

JP7632448B2Active Publication Date: 2025-02-19JSR CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2022503118
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-28
Filing Date
2020-12-23
Publication Date
2025-02-19
Estimated Expiration
2040-12-23

AI Technical Summary

Benefits of technology

【0009】 本開示によれば、上記重合体[P]を含有することにより、被分散体の分散性及び分散安定性に優れた分散組成物を得ることができる。また、被分散体の分散性及び分散安定性に優れた分散剤を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632448000001
    Figure 0007632448000001
  • Figure 0007632448000002
    Figure 0007632448000002
  • Figure 0007632448000003
    Figure 0007632448000003
Patent Text Reader

Abstract

A dispersion composition that contains a dispersed substance, a dispersion medium, and a polymer [P]. The polymer [P] is a partially imidized polyamic acid and has at least one type of specific structure selected from the group that consists of steroid structures and partial structures represented by formula (1). (1) *-L1-R1-R2-R3-R4 (in which L1 is a single bond, -O-, -COO-, or the like, R1 and R3 are a single bond, a substituted or unsubstituted phenylene group, or a substituted or unsubstituted cycloalkylene group, R2 is a single bond, a substituted or unsubstituted phenylene group, a substituted or unsubstituted cycloalkylene group, or the like, and R4 is a hydrogen atom, a C1–18 alkyl group, or the like).
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application is based on Japanese Patent Application No. 2020-33547, filed on February 28, 2020, the contents of which are incorporated herein by reference. [Technical field]

[0002] The present disclosure relates to dispersion compositions and dispersants. [Background technology]

[0003] Nano-order substances such as nanocarbons and metal nanoparticles have excellent properties in electrical properties, mechanical properties, thermal stability, etc., and are being considered for application and practical use in various fields as nanomaterials. These nanoparticles may be dispersed in a medium to utilize their functions, or nanoparticles dispersed in a liquid phase may be applied to a substrate to be used for the production of functional materials. In this case, in order to fully express the properties of the nanoparticles, it is desirable to uniformly disperse the particles in the dispersion medium. Therefore, as one method for suppressing the aggregation of nanoparticles and increasing the dispersibility of the particles, the use of polyimide as a polymer dispersant has been proposed (see, for example, Non-Patent Document 1). Non-Patent Document 1 discloses the use of polyimide having a diamine unit containing a sulfonic acid group as a dispersant for carbon nanotubes (CNTs). [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] "Overview of Carbon Nanotube Dispersion Technology", Journal of the Society of Rubber Industry, Japan, 2016, Vol. 89, No. 1, pp. 15-21 Summary of the Invention [Problem to be solved by the invention]

[0005] It cannot be said that polyimides having an anionic group on the side chain, such as the polyimide dispersant described in Non-Patent Document 1, have sufficiently high solubility in organic solvents. Therefore, when an organic solvent is used as a dispersion medium for dispersing a dispersed substance such as nanocarbon, the dispersant does not dissolve sufficiently in the dispersion medium, and there is a concern that the dispersibility of the dispersed substance and the dispersion stability over time will decrease.

[0006] The present disclosure has been made in consideration of the above problems, and has as its main object to provide a dispersion composition and a dispersant that are excellent in dispersibility and dispersion stability of a dispersed substance. [Means for solving the problem]

[0007] The present inventors have conducted intensive research to solve the above problems, and have found that the above problems can be solved by using an imidized polymer having a specific structure. That is, the present disclosure provides the following means.

[0008] <1> A dispersion composition comprising a dispersed substance, a dispersion medium, and a polymer [P] which is a partially imidized product of a polyamic acid and has at least one specific structure selected from the group consisting of a steroid structure and a partial structure represented by the following formula (1): *-L 1 -R 1 -R 2 -R 3 -R 4 …(1) (In formula (1), L 1 is a single bond, -O-, -CO-, -COO-* 1 , -OCO-* 1 , -NR 5 -, -NR 5 -CO-* 1 , -CO-NR 5 -* 1 , an alkanediyl group having 1 to 6 carbon atoms, -OR 6 -* 1 , or -R 6 -O-* 1 (However, R 5 is a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms, and R 6is an alkanediyl group having 1 to 3 carbon atoms. 1 " is R 1 It indicates that it is a bond with . ) R 1 and R 3 R is each independently a single bond, a substituted or unsubstituted phenylene group, or a substituted or unsubstituted cycloalkylene group. 2 represents a single bond, a substituted or unsubstituted phenylene group, a substituted or unsubstituted cycloalkylene group, or -R 7 -B 1 -R 8 -(However, R 7 and R 8 each independently represents a substituted or unsubstituted phenylene group or cycloalkylene group; B 1 is a single bond, -O-, -COO-* 2 , -OCO-* 2 , -OCH2-* 2 , -CH2O-* 2 or an alkanediyl group having 1 to 3 carbon atoms. 2 " is R 8 It indicates that it is a bond with . ) R 4 is a hydrogen atom, a fluorine atom, a cyano group, * 3 -OCO-CH3("* 3 " is R 3 ), an alkyl group having 1 to 18 carbon atoms, a fluoroalkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a fluoroalkoxy group having 1 to 18 carbon atoms, or a monovalent group in which at least one hydrogen atom of an alkyl group having 1 to 18 carbon atoms is substituted with a cyano group. 1 , R 2 and R 3 are all single bonds, or R 1 , R 2 and R 3 When the total number of benzene rings and cyclohexylene rings contained in R is 1, 4 is an alkyl group having 3 to 18 carbon atoms, a fluoroalkyl group having 3 to 18 carbon atoms, an alkoxy group having 3 to 18 carbon atoms, or a fluoroalkoxy group having 3 to 18 carbon atoms. "*" indicates a bond.) <2> A dispersant containing the above polymer [P]. Effect of the Invention

[0009] According to the present disclosure, by containing the polymer [P], a dispersion composition having excellent dispersibility and dispersion stability of a dispersed substance can be obtained. Also, a dispersant having excellent dispersibility and dispersion stability of a dispersed substance can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The dispersion composition of the present disclosure contains (A) a dispersed substance, (B) a dispersion medium, and (C) a polymer [P]. Each component contained in the dispersion composition of the present disclosure and other components that are optionally blended as necessary will be described below.

[0011] In this specification, the term "hydrocarbon group" includes chain-like hydrocarbon groups, alicyclic hydrocarbon groups, and aromatic hydrocarbon groups. The term "chain-like hydrocarbon group" refers to a straight-chain hydrocarbon group and a branched hydrocarbon group that do not include a cyclic structure in the main chain and are composed only of a chain structure. However, they may be saturated or unsaturated. The term "alicyclic hydrocarbon group" refers to a hydrocarbon group that includes only an alicyclic hydrocarbon structure as a ring structure and does not include an aromatic ring structure. However, it does not have to be composed only of an alicyclic hydrocarbon structure, and it also includes those that have a chain structure as a part of it. The term "aromatic hydrocarbon group" refers to a hydrocarbon group that includes an aromatic ring structure as a ring structure. However, it does not have to be composed only of an aromatic ring structure, and it may include a chain structure or an alicyclic hydrocarbon structure as a part of it.

[0012] <(A) Dispersed entity> The dispersed substance is a substance to be dispersed in a dispersion medium. The dispersed substance is not particularly limited, and at least one selected from the group consisting of inorganic particles and organic particles can be used. The shape of the dispersed substance is also not particularly limited, and examples thereof include spherical, rod-like, fibrous, flat, and disk-like shapes. The primary particle diameter of the dispersed substance is preferably 10 μm or less, more preferably 1 μm or less, and even more preferably 200 nm or less. The primary particle diameter of the dispersed substance is preferably 1 nm or more, more preferably 2 nm or more, and even more preferably 5 nm or more. The "primary particle diameter of the dispersed substance" referred to here is a value obtained by measuring the d50 value by a laser diffraction / scattering method.

[0013] Examples of inorganic particles contained in the dispersion composition of the present disclosure include carbon, metal particles, semi-metal particles, silica, inorganic salts, quantum dots, etc. Specific examples of these include carbon, such as carbon black, carbon fiber, carbon nanotubes, graphite, fullerene, carbon nanohorns, etc.; metal particles, such as simple metals, metal oxides, metal carbides, metal nitrides, etc.; semi-metal particles, such as semi-metal oxides, semi-metal carbides, semi-metal nitrides, etc.; silica, such as wet silica (hydrated silicic acid), dry silica (anhydrous silicic acid), colloidal silica, precipitated silica, calcium silicate, aluminum silicate, modified silica that has been subjected to surface modification treatment, etc.; inorganic salts, such as sulfates (calcium sulfate, barium sulfate, etc.), carbonates (calcium carbonate, magnesium carbonate, barium carbonate, etc.), phosphates (calcium phosphate, etc.), etc.; quantum dots, such as perovskite quantum dots, carbon-based quantum dots, lead sulfide quantum dots, etc., can be mentioned.

[0014] The carbon fibers include carbon nanofibers. The carbon nanotubes include single-wall carbon nanotubes, double-wall carbon nanotubes, and multi-wall carbon nanotubes. The carbon nanotubes may be made of only carbon, or may have a part of their structure substituted or chemically modified with other elements, or may be composites with metals (e.g., gold, silver, copper, aluminum, nickel, cobalt, titanium, platinum, etc.).

[0015] More specifically, the metal particles include particles containing metal elements such as gold, silver, copper, zinc, aluminum, tin, nickel, palladium, platinum, cobalt, iron, manganese, chromium, molybdenum, titanium, zirconium, hafnium, yttrium, and cerium. Specific examples of these include metal elements such as metal oxides, copper oxide, aluminum oxide, zinc oxide, iron oxide, titanium oxide, barium titanate, bismuth oxide, cerium oxide, chromium oxide, cobalt oxide, indium oxide, indium tin oxide, zirconium oxide, yttrium oxide, tin oxide, indium oxide-gallium oxide-zinc oxide, indium oxide-zinc oxide, and indium tin oxide; metal carbides such as titanium carbide; metal nitrides such as titanium nitride, titanium oxynitride (titanium black), and aluminum nitride. The metal particles can be used alone or in combination of two or more.

[0016] Examples of the semi-metallic particles include particles containing a semi-metallic element such as boron or silicon. Specific examples of these include simple metalloids consisting of the semi-metallic elements, metal oxides such as silicon dioxide, metal carbides such as boron carbide and silicon carbide, and metal nitrides such as boron nitride and silicon nitride. The semi-metallic particles can be used alone or in combination of two or more kinds.

[0017] Examples of organic particles include organic pigments, dichroic dyes, dye aggregates, proteins, nucleic acids, viruses, etc. Specific examples of these include organic pigments such as anthraquinone pigments, monoazo pigments, diazo pigments, benzimidazolone pigments, quinacridone pigments, quinophthalone pigments, dioxazine pigments, phthalocyanine pigments, flavanthrone pigments, indanthrone pigments, indolinone pigments, thioindigo pigments, metal complex pigments, perinone pigments, and perylene pigments; dichroic dyes such as disazo compounds, trisazo compounds, tetrakisazo compounds, anthraquinone compounds, and dioxazine compounds; and dye aggregates such as J aggregates of porphyrin dyes, cyanine dyes, pyrrolopyrrole dyes, acene dyes, and squarylium dyes, and H aggregates of oxazole yellow dyes, thiazole orange dyes, cyanine dyes, and azo dyes.

[0018] In one embodiment of the dispersion composition of the present disclosure, at least one type selected from the group consisting of metal particles and semimetal particles (hereinafter also referred to as "metal particles, etc.") can be preferably used as the dispersed substance. In another embodiment, at least one type selected from the group consisting of rod-shaped nanostructures and rod-shaped molecules (hereinafter also referred to as "rod-shaped nanostructures, etc.") can be preferably used as the dispersed substance. Examples of rod-shaped molecules include dichroic dyes, and examples of rod-shaped nanostructures include dye associations, quantum rods, metal nanorods, carbon nanotubes, proteins, nucleic acids, viruses, etc. When the dispersed substance is at least one type selected from the group consisting of rod-shaped nanostructures and rod-shaped molecules, inorganic particles can be preferably used as the dispersed substance, and carbon nanotubes and metal nanorods can be particularly preferably used. Note that, as the dispersed substance, one of the above can be used alone or two or more can be used in combination.

[0019] Of the above, inorganic particles can be preferably used as the dispersed material, and carbon nanotubes (CNTs) and metal particles can be particularly preferably used.

[0020] The content of the dispersed substance in the dispersion composition is appropriately set according to the type of dispersed substance, but is preferably 0.0001% by mass or more, more preferably 0.001% by mass or more, and even more preferably 0.003% by mass or more, based on the total amount of the dispersion composition. The content of the dispersed substance in the dispersion composition is preferably 60% by mass or less, more preferably 55% by mass or less, and even more preferably 50% by mass or less, based on the total amount of the dispersion composition.

[0021] More specifically, for example, when the dispersed object is a rod-shaped nanostructure, the content of the rod-shaped nanostructure in the dispersion composition is preferably 0.0001% by mass or more, more preferably 0.001% by mass or more, and even more preferably 0.003% by mass or more, based on the total amount of the dispersion composition, from the viewpoint of fully expressing the characteristics. Also, from the viewpoint of suppressing aggregation of the rod-shaped nanostructure caused by an excess of the rod-shaped nanostructure, the content of the rod-shaped nanostructure is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less, based on the total amount of the dispersion composition.

[0022] When the dispersed substance is metal particles, the content of the metal particles in the dispersion composition is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 3% by mass or more, based on the total amount of the dispersion composition. The content of the metal particles is preferably 60% by mass or less, more preferably 55% by mass or less, and even more preferably 50% by mass or less, based on the total amount of the dispersion composition.

[0023] <(B) Dispersion medium> The dispersion medium is a phase in which the substance to be dispersed is dispersed, and is preferably an organic solvent. The organic solvent is not particularly limited, and examples thereof include aprotic polar solvents, phenolic solvents, ketone solvents, ether solvents, ester solvents, alcohol solvents, halogenated hydrocarbon solvents, and hydrocarbon solvents.

[0024] Specific examples of these include aprotic polar solvents such as N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 1,3-dimethyl-1-imidazolidinone, γ-butyrolactone, γ-butyrolactam, N,N-dimethylformamide, N,N-dimethylacetamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N,N,2-trimethylpropanamide, acetonitrile, dimethylsulfoxide, tetramethylurea, and hexamethylphosphortriamide; Phenolic solvents include m-cresol, xylenol, and halogenated phenols; Ketone solvents include cyclobutanone, cyclopentanone, cyclohexanone, cycloheptanone, acetone, methyl ethyl ketone, methyl n-propyl ketone, methyl n-butyl ketone, diethyl ketone, di-n-butyl ketone, methyl i-butyl ketone, methyl n-pentyl ketone, ethyl n-butyl ketone, methyl n-hexyl ketone, diisobutyl ketone, and trimethylnonanone; Examples of ether solvents include partial ethers of polyhydric alcohols such as propylene glycol monomethyl ether (PGME), diethylene glycol diethyl ether (DEDG), diethylene glycol ethyl methyl ether, 3-methoxy-1-butanol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol-n-propyl ether, ethylene glycol-i-propyl ether, ethylene glycol-n-butyl ether (butyl cellosolve), 1-butoxy-2-propanol, ethylene glycol dimethyl ether, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, and dipropylene glycol monomethyl ether; partial esters of polyhydric alcohols such as diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate (PGMEA), and propylene glycol monoethyl ether acetate; and cyclic ethers such as tetrahydrofuran. Ester solvents such as methyl acetate, ethyl acetate, propyl acetate, n-butyl acetate, i-butyl acetate, sec-butyl acetate, t-butyl acetate, 3-methoxybutyl acetate, methyl acetoacetate, ethyl acetoacetate, ethyl propionate, butyl propionate, methyl lactate, ethyl lactate, butyl lactate, ethylene carbonate, and propylene carbonate; Alcohol-based solvents include methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, t-butanol, 1-pentanol, 3-methyl-1-butanol, 1-hexanol, 2-hexanol, heptanol, cyclohexanol, methylcyclohexanol, diacetone alcohol, propane-1,2-diol, and ethylene glycol; Halogenated hydrocarbon solvents include dichloromethane, 1,2-dichloroethane, 1,4-dichlorobutane, trichloroethane, etc.; Examples of the hydrocarbon solvent include hexane, heptane, octane, benzene, toluene, xylene, etc. As the dispersion medium, one type may be used alone, or two or more types may be used in combination.

[0025] Among the above, the aprotic polar solvent is preferred because it has high solubility for the polymer [P] and can provide excellent dispersibility and dispersion stability for the dispersed substance, and is particularly preferred to be at least one compound (hereinafter also referred to as "specific solvent") selected from the group consisting of N-methylpyrrolidone, N-ethylpyrrolidone, γ-butyrolactone, dimethylsulfoxide, N,N-dimethylformamide, and N,N-dimethylacetamide. The proportion of the aprotic polar solvent in the dispersion medium is preferably more than 50% by mass, more preferably 70% by mass or more, even more preferably 85% by mass or more, and particularly preferably 95% by mass or more, based on the total amount of the dispersion medium contained in the dispersion composition. The content of the specific solvent (the total amount when two or more types are contained) is preferably 50 mass% or more, more preferably 65 mass% or more, even more preferably 80 mass% or more, and particularly preferably 90 mass% or more, based on the total amount of the dispersion medium contained in the dispersion composition.

[0026] <(C) Polymer [P]> The dispersion composition of the present disclosure contains a polymer [P] which is a partially imidized product of a polyamic acid. The polymer [P] has at least one type (hereinafter also referred to as a "specific structure") selected from the group consisting of a steroid structure and a partial structure represented by the following formula (1): *-L 1 -R 1 -R 2 -R 3 -R 4 …(1) (In formula (1), L 1 is a single bond, -O-, -CO-, -COO-* 1 , -OCO-* 1 , -NR 5 -, -NR 5 -CO-* 1 , -CO-NR 5 -* 1 , an alkanediyl group having 1 to 6 carbon atoms, -OR 6 -* 1 , or -R 6 -O-* 1 (However, R 5 is a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms, and R 6 is an alkanediyl group having 1 to 3 carbon atoms. 1 " is R 1 It indicates that it is a bond with . ) R 1 and R 3 R is each independently a single bond, a substituted or unsubstituted phenylene group, or a substituted or unsubstituted cycloalkylene group. 2 represents a single bond, a substituted or unsubstituted phenylene group, a substituted or unsubstituted cycloalkylene group, or -R 7 -B 1 -R 8 -(However, R 7 and R 8 each independently represents a substituted or unsubstituted phenylene group or cycloalkylene group; B 1 is a single bond, -O-, -COO-* 2 , -OCO-* 2 , -OCH2-* 2, -CH2O-* 2 or an alkanediyl group having 1 to 3 carbon atoms. 2 " is R 8 It indicates that it is a bond with . ) R 4 is a hydrogen atom, a fluorine atom, a cyano group, * 3 -OCO-CH3("* 3 " is R 3 ), an alkyl group having 1 to 18 carbon atoms, a fluoroalkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a fluoroalkoxy group having 1 to 18 carbon atoms, or a monovalent group in which at least one hydrogen atom of an alkyl group having 1 to 18 carbon atoms is substituted with a cyano group. 1 , R 2 and R 3 are all single bonds, or R 1 , R 2 and R 3 When the total number of benzene rings and cyclohexylene rings contained in R is 1, 4 is an alkyl group having 3 to 18 carbon atoms, a fluoroalkyl group having 3 to 18 carbon atoms, an alkoxy group having 3 to 18 carbon atoms, or a fluoroalkoxy group having 3 to 18 carbon atoms. "*" indicates a bond.)

[0027] When the specific structure is a steroid structure, preferred specific examples thereof include structures having a cholestane skeleton, a cholestene skeleton, and a lanostane skeleton.

[0028] When the specific structure is a partial structure represented by the above formula (1), in the substituted phenylene group and substituted cycloalkylene group in the above formula (1), the substituent bonded to the ring is preferably an alkyl group having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, a fluorine atom, or a cyano group. The number of the substituents possessed by each of the substituted phenylene group and the substituted cycloalkylene group is preferably 1 or 2, and more preferably 1.

[0029] R 4is an alkyl group having 1 to 18 carbon atoms, a fluoroalkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a fluoroalkoxy group having 1 to 18 carbon atoms, or a monovalent group in which at least one hydrogen atom of an alkyl group having 1 to 18 carbon atoms is substituted with a cyano group, R 4 is preferably linear. The number of carbon atoms is preferably 2 or more, more preferably 3 or more, and further preferably 5 or more. R 1 , R 2 and R 3 are all single bonds, or R 1 , R 2 and R 3 When the total number of benzene rings and cyclohexylene rings contained in R is 1, the dispersibility and dispersion stability of the dispersed substance can be improved, which is preferable. 4 preferably has 4 or more carbon atoms, more preferably has 7 or more carbon atoms, and further preferably has 10 or more carbon atoms.

[0030] The structure represented by the above formula (1) preferably has a ring structure from the viewpoint of improving the dispersibility and dispersion stability of the dispersed substance. 1 , R 2 and R 3 The total number of benzene rings and cyclohexylene rings contained in the alkyl group is preferably 1 or more, more preferably 1 to 4, and even more preferably 2 to 4. In order to further increase the dispersibility and dispersion stability of the dispersed substance, the polymer [P] has the specific structure represented by the formula (1) R 1 , R 2 and R 3 It is preferable that the aryl group has at least one structure selected from the group consisting of a structure in which the total number of benzene rings and cyclohexylene rings is 2 or more and a steroid structure, and it is particularly preferable that the aryl group has at least a steroid structure.

[0031] The polymer [P] is a partial imidization product of polyamic acid, and has an amic acid structure and an imidization structure in one molecule. The method of synthesizing the polymer [P] is not particularly limited. The polymer [P] can be obtained, for example, by reacting a tetracarboxylic dianhydride with a diamine compound to synthesize a polyamic acid (hereinafter also referred to as "polyamic acid [P]") which is a precursor of the polymer [P], and then dehydrating and ring-closing the polyamic acid [P] to imidize a part of the amic acid structure of the polyamic acid [P].

[0032] (Synthesis of polyamic acid [P]) Tetracarboxylic acid dianhydride The tetracarboxylic dianhydride used in the synthesis of the polyamic acid [P] is not particularly limited, but examples thereof include aliphatic tetracarboxylic dianhydrides, alicyclic tetracarboxylic dianhydrides, and aromatic tetracarboxylic dianhydrides.

[0033] Specific examples of the tetracarboxylic dianhydride include aliphatic tetracarboxylic dianhydrides such as butanetetracarboxylic dianhydride and ethylenediaminetetraacetic dianhydride; Alicyclic tetracarboxylic dianhydrides include 1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutane tetracarboxylic dianhydride, 2,3,5-tricarboxycyclopentylacetic dianhydride, 5-(2,5-dioxotetrahydrofuran-3-yl)-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 5-(2,5-dioxotetrahydrofuran-3-yl)-8-methyl-3a,4,5,9b-tetrahydronaphtho[1,2-c]furan-1,3-dione, 3-oxabicyclo[3.2 .1]octane-2,4-dione-6-spiro-3'-(tetrahydrofuran-2',5'-dione), 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, 3,5,6-tricarboxy-2-carboxymethylnorbornane-2:3,5:6-dianhydride, bicyclo[3.3.0]octane-2,4,6,8-tetracarboxylic acid 2:4,6:8-dianhydride, bicyclo[2.2.1]heptane-2,3,5,6-tetracarboxylic acid 2:3,5:6-dianhydride, 4,9-dioxatricyclo[5.3.1.0]octane-2,4,6,8-tetracarboxylic acid 2:4,6:8-dianhydride, bicyclo[2.2.1]heptane-2,3,5,6-tetracarboxylic acid 2:3,5:6-dianhydride, 2,6 ]undecane-3,5,8,10-tetraone, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, etc.; Examples of aromatic tetracarboxylic dianhydrides include pyromellitic dianhydride, 4,4'-biphthalic dianhydride, 4,4'-carbonyldiphthalic dianhydride, 4,4'-oxydiphthalic dianhydride, naphthalene-1,4,5,8-tetracarboxylic dianhydride, naphthalene-1,4,5,6-tetracarboxylic dianhydride, ethylene glycol bis(anhydrotrimellitate), 1,3-propylene glycol bis(anhydrotrimellitate), and the like; In addition to the above, the tetracarboxylic dianhydrides described in JP-A-2010-97188 can also be used.

[0034] The tetracarboxylic dianhydride used in the synthesis of the polyamic acid [P] preferably contains an alicyclic tetracarboxylic dianhydride, since it improves the solubility of the polymer [P] in the dispersion medium and can further increase the dispersibility and dispersion stability of the dispersed substance. In the synthesis of the polyamic acid [P], the proportion of the alicyclic tetracarboxylic dianhydride used (i.e., the proportion of the structural unit (also referred to as "structural unit UA") derived from the alicyclic tetracarboxylic dianhydride in the polymer [P]) is preferably 5 mol% or more, more preferably 15 mol% or more, even more preferably 25 mol% or more, and particularly preferably 50 mol% or more, based on the total amount of the tetracarboxylic dianhydride used in the synthesis of the polyamic acid [P].

[0035] The alicyclic tetracarboxylic dianhydride used in the synthesis of the polyamic acid [P] is preferably at least one selected from the group consisting of 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 2,3,5-tricarboxycyclopentylacetic dianhydride, bicyclo[3.3.0]octane-2,4,6,8-tetracarboxylic 2:4,6:8-dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, and 1,2,3,4-cyclopentanetetracarboxylic dianhydride. The tetracarboxylic dianhydride may be used alone or in combination of two or more.

[0036] Diamine compounds The diamine compound used for synthesizing the polyamic acid [P] preferably contains a diamine having the above-mentioned specific structure (hereinafter also referred to as "specific diamine"). The method of polymerization using the specific diamine is preferable in that it is easy to synthesize a polymer having the above-mentioned specific structure and it is easy to adjust the content ratio of the above-mentioned specific structure in one polymer molecule. By polymerizing a monomer containing the specific diamine, a partially imidized product having a structural unit derived from the specific diamine (hereinafter also referred to as "structural unit UD") is obtained as the polymer [P].

[0037] The specific diamine may be any of aliphatic diamine, alicyclic diamine, and aromatic diamine as long as it has the above-mentioned specific structure. From the viewpoint of further increasing the dispersibility and dispersion stability of the dispersed substance, the specific diamine is preferably an aromatic diamine, and more preferably at least one selected from the group consisting of the compounds represented by the following formula (2) and the compounds represented by the following formula (3). [ka] (In formula (2), L 2 is a single bond, -O-, -CO-, -COO-* 4 , -OCO-* 4 , -NR 10 -, -NR 10 -CO-* 4 or -CO-NR 10 -* 4 (However, R 10 is a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms. 4 " is R 9 It indicates that it is a bond with . ) R 9 is a monovalent group having a steroid skeleton. [ka] (In formula (3), L 1 , R 1 , R 2 , R 3 and R 4 is defined as the above formula (1).

[0038] Specific examples of the specific diamine include compounds represented by the above formula (2), such as cholestanyloxy-3,5-diaminobenzene, cholesteryloxy-3,5-diaminobenzene, cholestanyloxy-2,4-diaminobenzene, cholesteryloxy-2,4-diaminobenzene, cholestanyl 3,5-diaminobenzoate, cholesteryl 3,5-diaminobenzoate, lanostannyl 3,5-diaminobenzoate, 3,6-bis(4-aminobenzoyloxy)cholestane, and 3,6-bis(4-aminophenoxy)cholestane; Examples of the compound represented by the above formula (3) include butanoxy-2,4-diaminobenzene, butanoxy-3,5-diaminobenzene, pentanoxy-2,4-diaminobenzene, pentanoxy-3,5-diaminobenzene, hexanoxy-3,5-diaminobenzene, heptanoxy-2,4-diaminobenzene, dodecanoxy-2,4-diaminobenzene, pentadecanoxy-2,4-diaminobenzene, hexadecanoxy-2,4-diaminobenzene, octadecanoxy-2,4-diaminobenzene, pentadecanoxy-2,5-diaminobenzene, octadecanoxy-2,5-diaminobenzene, 4-(4'-trifluoromethoxybenzoyloxy)cyclohexyl-3,5-diaminobenzoate, and the compound represented by the following formula (E-1): [ka] (In formula (E-1), X I and X II are each independently a single bond, -O-, *-COO- or *-OCO- (where "*" represents X I ) and R I is an alkanediyl group having 1 to 3 carbon atoms, and R II is a single bond or an alkanediyl group having 1 to 3 carbon atoms, and R 11 is a hydrogen atom, a fluorine atom, a cyano group, an alkyl group having 1 to 18 carbon atoms, a fluoroalkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, or a fluoroalkoxy group having 1 to 18 carbon atoms, a is an integer of 0 to 2, b is an integer of 0 to 2, and d is 0 or 1. However, a and b cannot be 0 at the same time. and the like.

[0039] Specific examples of the compound represented by formula (E-1) above include compounds represented by the following formulas (E-1-1) to (E-1-13), respectively. [ka] [ka] (In formulas (E-1-1) to (E-1-13), X 1 is -O-, -OCH2-, -CH2O-, -COO-CH2- or -CH2-OCO-; R 11 R has the same meaning as in formula (E-1). 12 is an alkyl group having 3 to 18 carbon atoms, a fluoroalkyl group having 3 to 18 carbon atoms, an alkoxy group having 3 to 18 carbon atoms, or a fluoroalkoxy group having 3 to 18 carbon atoms.

[0040] In the polyamic acid [P] and the polymer [P], the content of the structural unit UD derived from the specific diamine is preferably 1 mol% or more with respect to the total amount of the structural units derived from the diamine constituting the polymer. If the content of the structural unit UD is 1 mol% or more, it is preferable in that the effect of improving the dispersibility and dispersion stability of the dispersed substance by the introduction of the specific structure can be sufficiently obtained. From this viewpoint, the content of the structural unit UD is more preferably 2 mol% or more, and even more preferably 5 mol% or more with respect to the total amount of the structural units derived from the diamine constituting the polymer. In addition, from the viewpoint of suppressing the decrease in the solubility of the polymer in the dispersion medium, the content of the structural unit UD is preferably 95 mol% or less, more preferably 90 mol% or less, and even more preferably 80 mol% or less with respect to the total amount of the structural units derived from the diamine constituting the polymer. In addition, when synthesizing the polymer, the specific diamine may be used alone or in combination of two or more.

[0041] In the synthesis of the polyamic acid [P], only the specific diamine may be used as the diamine compound, but a diamine not having the specific structure (hereinafter also referred to as "other diamines") may be used together with the specific diamine. As the other diamine, from the viewpoint of not impairing the solubility of the polymer [P] in an organic solvent, a diamine having neither an anionic functional group nor a cationic functional group is preferable. In addition, from the viewpoint of further increasing the dispersibility and dispersion stability of the dispersed substance, the other diamine is preferably an aromatic diamine.

[0042] Specific examples of other diamines include aliphatic diamines such as metaxylylenediamine, 1,3-propanediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, and 1,3-bis(aminomethyl)cyclohexane; Alicyclic diamines, such as 1,4-diaminocyclohexane, 4,4'-methylenebis(cyclohexylamine), etc.; Aromatic diamines such as paraphenylenediamine, metaphenylenediamine, 4,4'-diaminodiphenylmethane, 4-aminophenyl-4'-aminobenzoate, 4,4'-diaminobenzanilide, 4,4'-diaminodiphenylamine, 4,4'-diaminoazobenzene, 1,5-bis(4-aminophenoxy)pentane, 1,7-bis(4-aminophenoxy)heptane, bis[2-(4-aminophenyl)ethyl]hexanedioic acid, N,N-bis(4-aminophenyl)methylamine, 1,5-diaminonaphthalene, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 2,7-diaminofluorene, 4,4'-diamino Main chain diamines such as diphenyl ether, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4'-(p-phenylenediisopropylidene)bisaniline, 4,4'-(m-phenylenediisopropylidene)bisaniline, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-[4,4'-propane-1,3-diylbis(piperidine-1,4-diyl)]dianiline, 1,4-bis(4-aminophenyl)piperazine, and 1,4-bis(4-amino(3-pyridinyl))piperazine; Examples of diaminoorganosiloxanes include 1,3-bis(3-aminopropyl)-tetramethyldisiloxane, and the like. In addition, diamines not having the partial structure represented by the above formula (1) among the diamines described in JP-A-2010-97188 can be used.

[0043] In the polyamic acid [P] and the polymer [P], the content of the structural unit derived from the other diamine (hereinafter also referred to as "structural unit UE") is preferably 99 mol% or less, more preferably 98 mol% or less, and even more preferably 95 mol% or less, based on the total amount of the structural units derived from the diamine constituting the polymer. The content of the structural unit UE is preferably 5 mol% or more, more preferably 10 mol% or more, and even more preferably 20 mol% or more, based on the total amount of the structural units derived from the diamine constituting the polymer. When synthesizing the polymer, one type of the other diamine may be used alone, or two or more types may be used in combination.

[0044] The polyamic acid [P] can be obtained by reacting the above-mentioned tetracarboxylic dianhydride with a diamine compound, optionally together with a molecular weight modifier. The ratio of the tetracarboxylic dianhydride and the diamine compound used in the synthesis reaction of the polyamic acid [P] is preferably such that the acid anhydride group of the tetracarboxylic dianhydride is 0.2 to 2 equivalents, more preferably 0.3 to 1.2 equivalents, per equivalent of the amino group of the diamine compound.

[0045] Examples of the molecular weight regulator include acid monoanhydrides such as maleic anhydride, phthalic anhydride, and itaconic anhydride, monoamine compounds such as aniline, cyclohexylamine, and n-butylamine, and monoisocyanate compounds such as phenyl isocyanate and naphthyl isocyanate. The proportion of the molecular weight regulator used is preferably 20 parts by mass or less, and more preferably 10 parts by mass or less, relative to 100 parts by mass in total of the tetracarboxylic dianhydride and diamine compounds used.

[0046] The synthesis reaction of the polyamic acid [P] is preferably carried out in an organic solvent. The reaction temperature is preferably from −20° C. to 150° C., more preferably from 0 to 100° C. The reaction time is preferably from 0.1 to 24 hours, more preferably from 0.5 to 12 hours.

[0047] Examples of organic solvents used in the reaction include aprotic polar solvents, phenolic solvents, alcohols, ketones, esters, ethers, halogenated hydrocarbons, and hydrocarbons. Of these organic solvents, it is preferable to use one or more selected from the group consisting of aprotic polar solvents and phenolic solvents (organic solvents of group 1), or a mixture of one or more selected from the organic solvents of group 1 and one or more selected from the group consisting of alcohols, ketones, esters, ethers, halogenated hydrocarbons, and hydrocarbons (organic solvents of group 2). In the latter case, the proportion of the organic solvents of group 2 used is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less, based on the total amount of the organic solvents of group 1 and group 2.

[0048] Particularly preferred organic solvents are one or more selected from the group consisting of N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethylsulfoxide, γ-butyrolactone, tetramethylurea, hexamethylphosphortriamide, m-cresol, xylenol and halogenated phenols, or a mixture of one or more of these with other organic solvents in the above ratio range. The amount (a) of the organic solvent used is preferably an amount such that the total amount (b) of the tetracarboxylic dianhydride and the diamine is 0.1 to 50 mass% based on the total amount (a+b) of the reaction solution.

[0049] (Imidization of polyamic acid [P]) To obtain the polymer [P], the polyamic acid [P] synthesized as described above is then imidized by dehydration and ring closure. The polymer [P] is a partially imidized product in which a part of the amic acid structure of the precursor polyamic acid [P] is dehydrated and ring closure is performed, and the amic acid structure and the imide ring structure coexist.

[0050] In terms of increasing the dispersibility and dispersion stability of the dispersed substance, the imidization rate of the polymer [P] is preferably 1% or more, more preferably 2% or more, even more preferably 5% or more, even more preferably 10% or more, and particularly preferably 20% or more. The imidization rate of the polymer [P] is preferably 98% or less, more preferably 95% or less, even more preferably 90% or less, even more preferably 85 mol% or less, and particularly preferably 80 mol% or less. The imidization rate of the polymer [P] is expressed as a percentage of the number of imide ring structures relative to the total number of amic acid structures and the number of imide ring structures of the polymer [P]. The details of the method for measuring the imidization rate are as follows in the following examples.

[0051] The dehydration ring-closure to obtain the polymer [P] is preferably carried out by a method of heating the polyamic acid [P], or by a method of dissolving the polyamic acid [P] in an organic solvent, adding at least one of a dehydrating agent and a dehydration ring-closure catalyst to the solution, and heating as necessary.

[0052] In the method of adding a dehydrating agent and a dehydration ring-closing catalyst to a solution of polyamic acid [P], for example, an acid anhydride such as acetic anhydride, propionic anhydride, or trifluoroacetic anhydride can be used as the dehydrating agent. The amount of the dehydrating agent used is preferably 0.01 to 20 moles per mole of the amic acid structure of the polyamic acid [P]. For example, a base catalyst such as pyridine, triethylamine, or 1-methylpiperidine, or an acid catalyst such as methanesulfonic acid or benzoic acid can be used as the dehydration ring-closing catalyst. The amount of the dehydration ring-closing catalyst used is preferably 0.01 to 10 moles per mole of the dehydrating agent used. Examples of the organic solvent used in the dehydration ring-closing reaction include the organic solvents exemplified as those used in the synthesis of polyamic acid [P]. The reaction temperature of the dehydration ring-closing reaction is preferably 0 to 200°C, more preferably 10 to 150°C. The reaction time is preferably 1.0 to 120 hours, more preferably 2.0 to 30 hours.

[0053] The reaction solution containing the polymer [P] may be used for preparing the dispersion composition as it is, or the polymer [P] contained in the reaction solution may be isolated and then used for preparing the dispersion composition, or the isolated polymer [P] may be purified and then used for preparing the dispersion composition. The isolation and purification of the polymer [P] can be carried out according to a known method. By using the (B) dispersion medium as the polymerization solution of the polymer [P], it is preferable in that the process can be simplified when preparing the dispersion composition.

[0054] The polymer [P] obtained as described above preferably has a solution viscosity of 10 to 2000 mPa·s, and more preferably 20 to 1000 mPa·s, when made into a 10% by mass solution. The solution viscosity (mPa·s) of the polymer is a value measured at 25°C using an E-type rotational viscometer for a 10% by mass polymer solution prepared using a good solvent for the polymer (e.g., N-methyl-2-pyrrolidone, γ-butyrolactone, etc.).

[0055] The weight average molecular weight (Mw) of the polymer [P] measured by gel permeation chromatography (GPC) in terms of polystyrene is preferably 1,000 to 500,000, more preferably 2,000 to 300,000. The molecular weight distribution (Mw / Mn), which is expressed as the ratio of Mw to the number average molecular weight (Mn) measured by GPC in terms of polystyrene, is preferably 15 or less, more preferably 10 or less.

[0056] Here, carbon nanotubes, which are one of the dispersed substances, have excellent properties such as electrical conductivity, heat resistance, toughness, and weight reduction. However, carbon nanotubes have high coagulation properties and are difficult to uniformly disperse in a dispersion medium. In addition, if the dispersion state of carbon nanotubes is not good, there is a concern that various properties of carbon nanotubes (e.g., electrical conductivity, resistance to external forces) will not be fully expressed in films, wiring, etc. obtained using the dispersion composition. In this regard, the dispersion composition of the present disclosure contains the polymer [P], and thus has excellent dispersibility of carbon nanotubes in a dispersion medium (especially an organic solvent). In addition, by using a dispersion composition containing carbon nanotubes and the polymer [P], a film, etc. with excellent electrical conductivity can be formed.

[0057] The content of the polymer [P] in the dispersion composition is appropriately selected in consideration of the type of the dispersed substance, but is preferably 1 part by mass or more, more preferably 3 parts by mass or more, relative to 100 parts by mass of the dispersed substance. The content of the polymer [P] is preferably 2000 parts by mass or less, more preferably 1500 parts by mass or less, and even more preferably 1000 parts by mass or less, relative to 100 parts by mass of the dispersed substance.

[0058] More specifically, for example, when the dispersed substance is a rod-shaped nanostructure, etc., from the viewpoint of sufficiently increasing the dispersibility of the rod-shaped nanostructure, etc., the content of the polymer [P] is preferably 100 parts by mass or more, more preferably 150 parts by mass or more, and even more preferably 200 parts by mass or more, relative to 100 parts by mass of the rod-shaped nanostructure, etc. Moreover, the content of the polymer [P] is preferably 2000 parts by mass or less, more preferably 1500 parts by mass or less, and even more preferably 1000 parts by mass or less, relative to 100 parts by mass of the rod-shaped nanostructure, etc.

[0059] When the dispersed substance is metal particles, etc., the content of the polymer [P] is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, relative to 100 parts by mass of the metal particles, etc. Also, the content of the polymer [P] is preferably 1000 parts by mass or less, more preferably 500 parts by mass or less, and even more preferably 300 parts by mass or less, relative to 100 parts by mass of the metal particles, etc.

[0060] It is not clear why the dispersibility and dispersion stability of the dispersed substance can be improved by incorporating polymer [P] into the dispersion composition. One hypothesis is that the aggregation of the dispersed substance is suppressed due to the excluded volume effect of the specific structure of polymer [P], and that the dispersion stability of the dispersed substance is improved by combining the electrostatic interaction due to the partially imidized polyamic acid with a conjugated structure.

[0061] <Other ingredients> The dispersion composition of the present disclosure may contain other components other than the dispersed substance, the dispersion medium, and the polymer [P] within a range that does not impede the purpose and effects of the present disclosure. Examples of other components include dispersants other than the polymer [P] (hereinafter also referred to as "other dispersants"), surfactants, fillers, defoamers, sensitizers, antioxidants, adhesion aids, antistatic agents, leveling agents, antibacterial agents, etc. The content ratio of other components can be appropriately set according to each compound to be blended within a range that does not impede the effects of the present disclosure.

[0062] In addition, when the dispersion composition of the present disclosure contains other dispersants, the content of the other dispersants is preferably 10 mass% or less, more preferably 5 mass% or less, and even more preferably 1 mass% or less, based on the total amount of the polymer [P] and other dispersants contained in the dispersion composition.

[0063] The method for preparing the dispersion composition is not particularly limited, and can be carried out according to a known method. For example, the dispersion composition can be prepared by mixing the substance to be dispersed, the dispersion medium, and the dispersant, and heating, stirring, etc. as necessary. The temperature when preparing the dispersion composition is preferably 5 to 90°C, more preferably 10 to 65°C. The treatment of mixing the substance to be dispersed, the dispersion medium, and the dispersant may be carried out using a homogenizer, a bead mill, etc.

[0064] The solid content concentration of the dispersion composition (i.e., the ratio of the total mass of the components other than the dispersion medium of the dispersion composition to the total mass of the dispersion composition) is appropriately selected in consideration of the viscosity, volatility of the dispersion medium, etc. For example, when the dispersed substance is carbon, the solid content concentration is preferably in the range of 0.1 to 30 mass%, more preferably in the range of 0.5 to 20 mass%, and even more preferably in the range of 1 to 15 mass%. Moreover, when the dispersed substance is metal particles, the solid content concentration is preferably in the range of 1 to 70 mass%, more preferably in the range of 2 to 65 mass%, and even more preferably in the range of 5 to 60 mass%.

[0065] The dispersion composition of the present disclosure uses a polymer [P] as a polymer dispersant. This suppresses aggregation of the dispersed substance in the dispersion medium, and allows the dispersed substance to be uniformly dispersed. The dispersion composition of the present disclosure is applied to a substrate, and preferably heated to remove the dispersion medium, thereby forming a thin film containing the dispersed substance on the substrate. The dispersion composition of the present disclosure can also be used in a liquid state as it is or by mixing with another dispersion liquid.

[0066] The dispersion composition and dispersant of the present disclosure can be used for various applications depending on the type of the dispersed substance. Specifically, they can be used for transparent conductive films, antistatic films, insulating films, protective films, antireflective films, colored films, field effect transistors (FETs), touch panels, conductive inks, paints, printing inks, inkjet coating inks, etc. EXAMPLES

[0067] The present invention will be described in more detail below with reference to examples, but is not limited to these examples. In the following examples, the imidization rate of the polymer was measured by the following method. The required amounts of the raw material compounds and polymers used in the following examples were ensured by repeating the synthesis on a synthesis scale shown in the following synthesis examples as necessary.

[0068] [Imidization rate of polymer] The solution containing the polymer was poured into pure water, and the resulting precipitate was thoroughly dried under reduced pressure at room temperature. It was then dissolved in deuterated dimethyl sulfoxide and measured at room temperature (25°C) using tetramethylsilane as a standard substance. 1 H-NMR was measured. 1 The imidization rate was calculated from the H-NMR spectrum using the following formula (EX-1). Imidization rate (%) = (((1-E 1 ) / E 2 )×α)×100 …(EX-1) (In formula (EX-1), E 1 is the peak area due to the proton of the NH group that appears at a chemical shift of around 10 ppm, and E 2 is the peak area due to other protons, and α is the ratio of the number of other protons to one proton of the NH group in the polymer precursor (polyamic acid). In the following, the compound represented by formula (X) may be simply abbreviated as "compound (X)".

[0069] 1. Polymer synthesis [Synthesis Example 1: Synthesis of polyamic acid] 33.4g (95 mol parts) of 2,3,5-tricarboxycyclopentylacetic dianhydride, 16.4g (20 mol parts) of cholestanyl 3,5-diaminobenzoate, and 25.1g (80 mol parts) of 4,4'-diaminodiphenyl ether were dissolved in 425g of N-methyl-2-pyrrolidone (NMP) and reacted at room temperature for 6 hours. The reaction mixture was poured into a large excess of methanol to precipitate the reaction product. The precipitate was washed with methanol and dried under reduced pressure at 40°C for 15 hours to obtain 67g of polyamic acid (hereinafter referred to as "polymer (paa-1)").

[0070] [Synthesis Example 2: Synthesis of polyimide] Similarly to the above, 95 mol parts of 2,3,5-tricarboxycyclopentylacetic dianhydride, 20 mol parts of cholestanyl 3,5-diaminobenzoate, and 80 mol parts of 4,4'-diaminodiphenyl ether were dissolved in N-methyl-2-pyrrolidone (NMP) to obtain a polyamic acid solution with a polymer concentration of 15% by mass. NMP was added to the obtained polyamic acid solution to dilute it so that the polymer concentration was 10% by mass, and then a predetermined amount of pyridine and acetic anhydride were added and reacted at 110°C for 4 hours. The obtained reaction mixture was then poured into a large excess of methanol to precipitate the reaction product. The collected precipitate was washed with methanol and then dried at 100°C under reduced pressure to obtain a polyimide (hereinafter referred to as "polymer (PI-1)"). The imidization rate of the obtained polymer (PI-1) was 50%.

[0071] [Synthesis Examples 3-13] Polyimides (polymers (PI-2) to (PI-10), (pi-1), and (pi-2)) were obtained in the same manner as in Synthesis Example 2, except that the types and amounts of tetracarboxylic dianhydrides and diamine compounds used in the reaction were changed as shown in Table 1 below. The imidization ratios of each polyimide are also shown in Table 1 below.

[0072] [Table 1]

[0073] The numerical values ​​in Table 1 show the proportion (mol %) of tetracarboxylic dianhydrides to the total amount of tetracarboxylic dianhydrides used in the reaction, and the numerical values ​​in Table 1 show the proportion (mol %) of diamine compounds to the total amount of diamine compounds used in the reaction. The abbreviations of tetracarboxylic dianhydrides and diamine compounds in Table 1 are as follows. (Tetracarboxylic acid dianhydride) AN-1; Bicyclo[3.3.0]octane-2,4,6,8-tetracarboxylic acid 2:4,6:8-dianhydride AN-2; 2,3,5-tricarboxycyclopentylacetic dianhydride AN-3; Pyromellitic dianhydride (Diamine compounds) DA-1; cholestanyl 3,5-diaminobenzoate DA-2; Cholestanyloxy-2,4-diaminobenzene DA-3: A compound represented by the following formula (DA-3): DA-4: A compound represented by the following formula (DA-4): DA-5; Paraphenylenediamine DA-6; 4,4'-diaminodiphenyl ether DA-7: A compound represented by the following formula (DA-7): DA-8: A compound represented by the following formula (DA-8): [ka]

[0074] 2. Preparation and evaluation of CNT-containing dispersion composition [Example 1] (1) Preparation of Dispersion Composition 10,000 parts by mass of NMP was added as a solvent to a container containing 50 parts by mass of single-walled carbon nanotubes (SWNT) and 250 parts by mass of the polymer (PI-1) obtained in Synthesis Example 2. Then, ultrasonic dispersion was carried out for 60 minutes to prepare a dispersion composition (S-1).

[0075] (2) Evaluation of CNT dispersibility The dispersion composition (S-1) obtained in (1) above was left to stand on a flat surface in an environment of 25°C. The evaluation was as follows: if the CNTs remained in their initial dispersion state without settling after one week of standing, it was rated "best (◎◎)"; if the CNTs remained in their initial dispersion state without settling after three days, but then settling or aggregation of the CNTs was observed, it was rated "excellent (◎)"; if the CNTs remained in their initial dispersion state without settling after one day, but then settling or aggregation of the CNTs was observed, it was rated "good (○)"; if the CNTs remained in their initial dispersion state without settling after three hours, but then settling or aggregation of the CNTs was observed, it was rated "fair (△)"; and if the CNTs remained in their initial dispersion state without settling after three hours of standing, it was rated "poor (×)". As a result, the CNT dispersibility of this dispersion composition (S-1) was "best (◎◎)".

[0076] (3) Evaluation of CNT dispersion stability (durability) A dispersion composition was prepared in the same manner as in (1) above. The obtained dispersion composition was left to stand on a flat surface in an environment of 40°C, and the dispersion state over time was observed. The evaluation was as follows: if the CNTs remained in the initial dispersion state without settling after one week of standing, it was rated "best (◎◎)"; if the CNTs remained in the initial dispersion state without settling after three days, but then settling or aggregation of the CNTs was observed, it was rated "excellent (◎)"; if the CNTs remained in the initial dispersion state without settling after one day, but then settling or aggregation of the CNTs was observed, it was rated "good (○)"; if the CNTs remained in the initial dispersion state without settling after three hours, but then settling or aggregation of the CNTs was observed, it was rated "fair (△)"; and if settling or aggregation was observed before three hours had passed after standing, it was rated "poor (×)". As a result, the CNT dispersion stability of the dispersion composition was "best (◎◎)".

[0077] (4) Evaluation of CNT coatability The dispersion composition (S-1) obtained in (1) above was applied onto a glass substrate using a blade, and dried on a hot plate at 80°C for 10 minutes to form a coating film having a thickness of 1 μm at the center of the substrate. This coating film was observed under a microscope at a magnification of 50 times to check for unevenness in the coating film thickness and the presence or absence of pinholes. The coating property was evaluated as "good (○)" when neither unevenness in the coating film thickness nor pinholes were observed, and as "poor (×)" when at least one of unevenness in the coating film thickness and pinholes was clearly observed. As a result, neither unevenness in the coating film thickness nor pinholes were observed, and the coating property was "good (○)".

[0078] (5) Evaluation of volume resistivity The dispersion composition (S-1) was applied and dried on a glass substrate in the same manner as in (4) above, except that the blade gap was changed, to obtain a film-like test piece. If necessary, the film thickness was adjusted to about 20 μm by applying it multiple times. Next, the volume resistivity (μΩ·m) of the obtained test piece was measured by the four-terminal method. The volume resistivity was calculated from the surface resistivity and film thickness using the following formula (EX-2). In addition, the measurement was performed five times while changing the measurement location, and the average value of the measurements was evaluated as the volume resistivity. Volume resistivity (μΩ m) = surface resistivity (Ω) x film thickness (μm) …(EX-2) As a result, the volume resistivity of the film obtained using the dispersion composition (S-1) was 280 μΩ·m. Note that the lower the volume resistivity of the film, the higher the conductivity.

[0079] (6) Testing the resistance of coating to external forces The dispersion composition (S-1) obtained in (1) above was applied to a glass substrate using a blade, and dried on a hot plate at 80°C for 10 minutes to form a coating film with an average thickness of 10 μm. The obtained coating film was examined for its resistance to cracking against mechanical external forces (external force resistance) by dropping a marble with a radius of 5 mm from a height of 20 cm. The evaluation was as follows: if no cracks were observed under a microscope (magnification: 10 times), it was rated as "good (○)"; if no cracks were observed visually but cracks were observed under a microscope, it was rated as "fair (△)"; and if cracks were observed visually, it was rated as "poor (×)". As a result, the external force resistance of the coating film formed using the dispersion composition (S-1) was judged to be "good (○)".

[0080] (7) Evaluation of substrate adhesion The dispersion composition (S-1) was applied to a glass substrate and dried to form a coating film having a thickness of 5 μm on the glass substrate in the same manner as in (4) above, except that the dispersion composition was applied by spray coating, thereby preparing a substrate with carbon nanotubes. Next, the substrate with carbon nanotubes was immersed for 10 seconds in a solvent prepared so that NMP / butyl cellosolve / propylene glycol monomethyl ether acetate = 5 / 25 / 70 (mass ratio), and then the substrate was dried on a hot plate at 80 ° C. for 10 minutes. The obtained substrate (hereinafter referred to as "test piece for adhesion evaluation") was observed under a microscope (magnification: 10 times) and the volume resistivity was evaluated to evaluate the substrate adhesion. The evaluation was as follows: "Best quality (◎◎)" if all of the following criteria 1, 2, and 3 were met; "Excellent (◎)" if criteria 1 and 2 were met but criterion 3 was not met; "Good (○)" if criteria 1 was met but criterion 2 was not met; "Fair (△)" if criteria 2 was met but criterion 1 was not met; and "Poor (×)" if criteria 1 and 2 were not met. Criterion 1: No cracks are observed when the test piece for adhesion evaluation is observed under a microscope. Criterion 2: The volume resistivity of the test piece for adhesion evaluation, calculated according to the method (EX-2) above, is 0.05 Ω·cm or less (500 μΩ·m or less). Criterion 3: The volume resistivity of the test piece for evaluating adhesion, determined according to the method of (EX-2) above, is equal to or less than the volume resistivity value of (EX-2) above. As a result, the substrate adhesion of the dispersion composition (S-1) was rated as "best (◎)".

[0081] (8) Evaluation of surface roughness The dispersion composition (S-1) was applied and dried on a 50 mm square glass substrate in the same manner as in (4) above, and a coating film having a thickness of 10.0 μm at the center of the substrate was formed on the glass substrate, thereby preparing a substrate with carbon nanotubes. Next, the film thickness was measured at points 5 mm inward from each of the four corners of the substrate, and the surface unevenness was evaluated based on the difference (μm) between the maximum film thickness and the minimum film thickness. The evaluation was made as "good (○)" when the difference between the maximum film thickness and the minimum film thickness was less than 2.0 μm, and "poor (×)" when it was 2.0 μm or more. As a result, the surface unevenness of the dispersion composition (S-1) was "good (○)".

[0082] [Examples 2 to 10, Comparative Examples 1 to 3] Except for changing the composition of the dispersion composition as shown in Table 2 below, dispersion compositions (S-2) to (S-10) and (sr-1) to (sr-3) were prepared in the same manner as the dispersion composition (S-1) of Example 1. In addition, various evaluations were performed in the same manner as Example 1, except for using the dispersion compositions (S-2) to (S-10) and (sr-1) to (sr-3) instead of the dispersion composition (S-1). The evaluation results of Examples 1 to 10 and Comparative Examples 1 to 3 are summarized in Table 2 below.

[0083] [Table 2]

[0084] In Table 2, the numerical values ​​for "blended amount" indicate parts by mass. The abbreviations for CNT are as follows. <cnt> MWNT; Multi-wall carbon nanotube DWNT; double-walled carbon nanotubes SWNT; Single-walled carbon nanotubes

[0085] From the results in Table 2, in Examples 1 to 10, the dispersibility of carbon nanotubes, dispersion stability, coatability, adhesion to substrate, surface unevenness, and resistance to external forces were evaluated as excellent, good, good, or fair. Of these, Examples 1 to 7 and 9 were superior in various properties to Examples 8 and 10. In particular, Examples 1, 6, and 7 were evaluated as "excellent" for CNT dispersibility and CNT dispersion stability, and also had a small volume resistivity of 450 μΩ·m or less, which was good. In addition, by using a dispersion composition with good dispersibility and dispersion stability, it was possible to form a film with good adhesion to the substrate, little surface unevenness, and high in-plane uniformity.

[0086] 3. Preparation and evaluation of metal particle-containing dispersion composition [Example 11] (1) Preparation of Dispersion Composition 53 parts by mass of NMP as a solvent was added to a container containing 45 parts by mass of titanium oxide as metal particles and 2 parts by mass of the polymer (PI-1) obtained in Synthesis Example 2. The mixture was then shaken for 10 minutes with a paint shaker to prepare a dispersion composition (S-11).

[0087] (2) Evaluation of particle dispersibility The dispersion composition (S-11) obtained in (1) above was left to stand on a flat surface in an environment of 25° C. for one day, and the dispersibility of the dispersed object (metal particles in this example) was evaluated in the same manner as in (2) of Example 1. As a result, the particle dispersibility of the dispersion composition (S-11) was "best (◎◎)". (3) Evaluation of particle dispersion stability (durability) A dispersion composition was prepared in the same manner as in (1) above. The obtained dispersion composition was left to stand on a flat surface in an environment of 40°C, and the dispersion stability of the dispersed substance was evaluated in the same manner as in (3) of Example 1. As a result, the dispersion stability of the dispersion composition of this example was "best (◎◎)".

[0088] (4) Evaluation of particle coating properties The coating property was evaluated in the same manner as in (4) of Example 1, except that the dispersion composition (S-11) obtained in (1) above was used. As a result, neither unevenness in film thickness nor pinholes were observed, and the coating property was "good (◯)". (5) Testing the resistance of coating to external forces Except for using the dispersion composition (S-11) obtained in (1) above, the coating film was subjected to an external force resistance test in the same manner as in (6) of Example 1 to confirm the resistance to cracking (external force resistance). As a result, the coating film formed using the dispersion composition (S-11) showed no cracks when observed under a microscope (magnification: 10 times), and the external force resistance was judged to be "good (○)".

[0089] [Examples 12 to 21, Comparative Examples 4 and 5] Except for changing the composition of the dispersion composition as shown in Table 3 below, the dispersion compositions (S-12) to (S-21) and (sr-4) and (sr-5) were prepared in the same manner as the dispersion composition (S-11) of Example 11. In addition, except for using the dispersion compositions (S-12) to (S-21) and (sr-4) and (sr-5) instead of the dispersion composition (S-11), various evaluations were performed in the same manner as Example 11. The evaluation results of Examples 12 to 21 and Comparative Examples 4 and 5 are summarized in Table 3 below.

[0090] [Table 3]

[0091] In Table 3, the numerical values ​​for "blended amount" indicate parts by mass. The abbreviations for the compounds are as follows. <Dispersant> BYK180; BYK-Chemie DISPERBYK-180 (polyacrylic dispersant)

[0092] From the results in Table 3, Examples 11 to 21 were evaluated as excellent, good, good or fair in terms of dispersibility of metal particles, dispersion stability, coatability and resistance to external forces. Among these, Examples 11 to 17 and 19 to 21, which contained polyimide having an alicyclic tetracarboxylic dianhydride unit, were superior in various properties compared to Example 18, which contained polyimide using only aromatic tetracarboxylic dianhydride as the acid dianhydride. In particular, Examples 11, 16, 17 and 19 to 21 were evaluated as "excellent" in both dispersibility and dispersion stability of metal particles, and the polyimide used in each Example was excellent in dispersant properties.< / cnt>

Claims

1. A dispersed object; A dispersion medium; a polymer [P] which is a partial imidization product of a polyamic acid and has at least one specific structure selected from the group consisting of a steroid structure and a partial structure represented by the following formula (1); Contains The dispersion composition, wherein the dispersed substance is a carbon nanotube. *-L 1 -R 1 -R 2 -R 3 -R 4 …(1) (In formula (1), L 1 represents a single bond, -O-, -CO-, -COO-* 1 , -OCO-* 1 , -NR 5 --, --NR 5 -CO-* 1 , —CO—NR 5 -* 1 an alkanediyl group having 1 to 6 carbon atoms; 6 -* 1 , or -R 6 -O-* 1 (However, R 5 is a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms, R 6 is an alkanediyl group having 1 to 3 carbon atoms. 1 " is R 1 It indicates that it is a bond with . 1 and R 3 R is each independently a single bond, a substituted or unsubstituted phenylene group, or a substituted or unsubstituted cycloalkylene group. 2 represents a single bond, a substituted or unsubstituted phenylene group, a substituted or unsubstituted cycloalkylene group, or -R 7 -B 1 -R 8 - (However, R 7 and R 8 each independently represents a substituted or unsubstituted phenylene group or cycloalkylene group; B 1 is a single bond, -O-, -COO-* 2 , -OCO-* 2 , -OCH 2 -* 2 , -CH 2 O-* 2 or an alkanediyl group having 1 to 3 carbon atoms. 2 " is R 8 It indicates that it is a bond with . 4 is a hydrogen atom, a fluorine atom, a cyano group, * 3 -OCO-CH 3 ("* 3 " is R 3 ), an alkyl group having 1 to 18 carbon atoms, a fluoroalkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a fluoroalkoxy group having 1 to 18 carbon atoms, or an alkyl group having 1 to 18 carbon atoms, at least one hydrogen atom of which is substituted with a cyano group. 1 , R 2 and R 3 are all single bonds, or R 1 , R 2 and R 3 When the total number of benzene rings and cyclohexylene rings contained in R is 1, 4 is an alkyl group having 3 to 18 carbon atoms, a fluoroalkyl group having 3 to 18 carbon atoms, an alkoxy group having 3 to 18 carbon atoms, or a fluoroalkoxy group having 3 to 18 carbon atoms. "*" indicates a bond.)

2. The polymer [P] contains a structural unit UD derived from a diamine having the specific structure, 2. The dispersion composition according to claim 1, wherein the content of the structural unit UD relative to the total amount of structural units derived from diamine constituting the polymer [P] is 1 mol % or more and 95 mol % or less.

3. The dispersion composition according to claim 1 or 2, wherein the imidization rate of the polymer [P] is 2% or more and 95% or less.

4. The dispersion composition according to any one of claims 1 to 3, wherein the polymer [P] has a structural unit UA derived from an alicyclic tetracarboxylic dianhydride.

5. The dispersion composition according to claim 4, wherein the content of the structural unit UA relative to the total amount of structural units derived from tetracarboxylic dianhydride constituting the polymer [P] is 5 mol % or more.

6. The dispersion composition according to any one of claims 1 to 5, wherein the dispersion medium comprises an aprotic polar solvent.

7. The dispersion medium comprises at least one selected from the group consisting of N-methylpyrrolidone, N-ethylpyrrolidone, γ-butyrolactone, dimethylsulfoxide, N,N-dimethylformamide, and N,N-dimethylacetamide. The dispersion composition according to any one of claims 1 to 6.

8. The dispersion composition according to any one of claims 1 to 7, wherein the content of the polymer [P] is 100 parts by mass or more and 2000 parts by mass or less with respect to 100 parts by mass of the dispersed substance.

9. A dispersant for carbon nanotubes for dispersing carbon nanotubes in a dispersion medium, comprising: A dispersant for carbon nanotubes comprising a polymer [P] which is a partially imidized product of a polyamic acid and has at least one specific structure selected from the group consisting of a steroid structure and a partial structure represented by the following formula (1): *-L 1 -R 1 -R 2 -R 3 -R 4 …(1) (In formula (1), L 1 represents a single bond, -O-, -CO-, -COO-* 1 , -OCO-* 1 , -NR 5 --, --NR 5 -CO-* 1 , —CO—NR 5 -* 1 an alkanediyl group having 1 to 6 carbon atoms; 6 -* 1 , or -R 6 -O-* 1 (However, R 5 is a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms, R 6 is an alkanediyl group having 1 to 3 carbon atoms. 1 " is R 1 It indicates that it is a bond with . 1 and R 3 R is each independently a single bond, a substituted or unsubstituted phenylene group, or a substituted or unsubstituted cycloalkylene group. 2 represents a single bond, a substituted or unsubstituted phenylene group, a substituted or unsubstituted cycloalkylene group, or -R 7 -B 1 -R 8 - (However, R 7 and R 8 each independently represents a substituted or unsubstituted phenylene group or cycloalkylene group; B 1 is a single bond, -O-, -COO-* 2 , -OCO-* 2 , -OCH 2 -* 2 , -CH 2 O-* 2 or an alkanediyl group having 1 to 3 carbon atoms. 2 " is R 8 It indicates that it is a bond with . 4 is a hydrogen atom, a fluorine atom, a cyano group, * 3 -OCO-CH 3 ("* 3 " is R 3 ), an alkyl group having 1 to 18 carbon atoms, a fluoroalkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a fluoroalkoxy group having 1 to 18 carbon atoms, or an alkyl group having 1 to 18 carbon atoms, at least one hydrogen atom of which is substituted with a cyano group. 1 , R 2 and R 3 are all single bonds, or R 1 , R 2 and R 3 When the total number of benzene rings and cyclohexylene rings contained in R is 1, 4 is an alkyl group having 3 to 18 carbon atoms, a fluoroalkyl group having 3 to 18 carbon atoms, an alkoxy group having 3 to 18 carbon atoms, or a fluoroalkoxy group having 3 to 18 carbon atoms. "*" indicates a bond.)

Citation Information

Patent Citations

  • Aqueous dispersion and its production

    JP1999060947A

  • Printed wiring board and its manufacturing method

    JP2003163444A